1999
DOI: 10.1002/1529-0131(199902)12:1<42::aid-art7>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

The fibromyalgia impact questionnaire: A useful tool in evaluating patients with post-Lyme disease syndrome

Abstract: Objective. To determine the reliability and validity of a modified version of the Fibromyalgia Impact Questionnaire (FIQ) in evaluating patients with post-Lyme disease syndrome (PLDS). Methods. In this cross-sectional analysis 13 PLDS, 18 fibromyalgia (FM), and 16 healthy controls (n 47) completed a modified FIQ containing items to evaluate physical impairment, symptom severity, and global well-being. Comparisons between groups were done using analysis of variance with a significance level set at 0.05. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
1
8
0
1
Order By: Relevance
“…There are few studies analyzing the factors that might affect the impact of the disease itself in FMS patients. In those studies, the FIQ correlated with depressed mood [18] and the number of tender points [28] similar to our findings. Since musculoskeletal disorders and related symptoms directly affect patients' functional activities, the relationship between pain and sleep disorder is understandable with FIQ.…”
Section: Discussionsupporting
confidence: 91%
“…There are few studies analyzing the factors that might affect the impact of the disease itself in FMS patients. In those studies, the FIQ correlated with depressed mood [18] and the number of tender points [28] similar to our findings. Since musculoskeletal disorders and related symptoms directly affect patients' functional activities, the relationship between pain and sleep disorder is understandable with FIQ.…”
Section: Discussionsupporting
confidence: 91%
“…The FIQ is a 19-item self-report instrument with a mean of 50 and SD of 10 where higher scores indicate worse functioning38. A version of the FIQ modified for Lyme disease patients was used39.…”
Section: Methodsmentioning
confidence: 99%
“…This version of the FIQ has been validated for patients who have persistent symptoms after treatment for Lyme disease. 13 In a control population without chronic illness, the mean total score on the modified FIQ was 14.0, whereas the mean for patients with chronic Lyme disease after treatment was 50.2. 13 Previous studies have indicated that a change of 16.0 points is clinically meaningful.…”
Section: Clinical Responsementioning
confidence: 96%
“…7,8 Additional measures of the health-related quality of life included the MOS scales for pain, cognition, and role functioning (the ability to participate in usual daily activities) 9-11 and a modified version of the Fibromyalgia Impact Questionnaire (FIQ). 12,13 Each of the instruments used to measure the health-related quality of life was administered to study participants at base line and at 30, 90, and 180 days. The SF-36 includes eight multiple-item scales that measure physical functioning, physical limitations on usual role-related activities, bodily pain, general health perceptions, vitality, social functioning, emotional limitations on usual role-related activities, and mental health.…”
Section: Clinical Responsementioning
confidence: 99%
See 1 more Smart Citation